Adaptive Integral Sliding Mode Controller for Longitudinal Rotation Control of a Tilt-Rotor Aircraft - Kim TH; Gadsden SA; Wilkerson SA (Institute of Electrical and Electronics Engineers (IEEE), 2016)
This paper presents an adaptive integral sliding mode controller for longitudinal rotation control of a tilt-rotor aircraft (TRA). The movable mass, which slides along the wing of the TRA, is considered an unknown disturbance in this paper. The simplified dynamics of the TRA is proposed for the control of the longitudinal rotation during its landing, and application of the adaptive integral sliding mode controller is presented. In the design process of the controller, we applied a sliding surface including an integral term for reinforcing the control performance of the system. This paper compares the results of applying a PID controller and the adaptive integral sliding mode controller with the proposed sliding surface for improved robustness and stability to unknown disturbance.
Keywords: 4007 Control Engineering, Mechatronics and Robotics; 40 Engineering; 4001 Aerospace Engineering; 4010 Engineering Practice and Education